Abul-Fazl governance and administration during the reign of Jalal-ud-din Mohammad Akbar (Journal of history-rus, 2021)
Abul-Fazl was the best friend and vizier of Jalal-ud-din Mohammad Akbar the third king of Moghul dynasty in India from (1556 – 1605), he is the author of famous book well known the Akbarnama, that was the official history of Akbar’s reign in three volumes, also he is author of another book the Ain-i- Ak- bari and a Persian translation of the Bible. He was also the brother of Faizi, the poet laureate of Emperor Akbar. In this article we will know how the emperor of Mughal dynasty who originally went from Af- ghanistan to north India and built a huge empire beginning in 1526 by grandfather of Akbar Zahirudding Mohammad Babur, it lasted more than two centuries. The Mughal become one of the most important dynasties of the subcontinent. The splendor and luxury of the courts, the policies of the emperors and the system of administration and taxation that the Mughals established have had a deep impact. Akbar widely considered the greatest of the Mughal emperors, was only 14 years old when he ascended the throne in Delhi, following the death of his father Humayun.Key words: Akbar, imperial court, emperor, subcontinent and Mughal dynasty